Measuring Islamic Modernity: Between Positive Alarms or Setbacks for Democracy in Indonesia - Imam Prayogo; Alin Fithor; Rosazman Hussin (Universitas Muhammadiyah Yogyakarta, 2023)
Researchers have intensively studied Islamic modernity since the movement has become a reasonably effective tool in mobilizing the masses and seeking political support. Almost 90 percent of Indonesian people are Muslim. The concept of Indonesia in making policies on state issues has resulted in a deadlocked relationship between its people and the concept of a state that tends toward the Dutch colonial nation. Islam is a characteristic of Indonesian society; however, the state does not use the concept in Islam. Hence, the concept of the state not being in line with society has resulted in today’s Indonesian people living full of poverty, even though they live in a country with abundant earth, air, and water wealth, coupled with captivating and unique seas for the world to see. However, how does the modern measure of Islam in Indonesia affect democracy? Using qualitative descriptive research methods with a literature study approach, this study discovered that modern Islam in Indonesia has various motives when viewed from multiple aspects used to describe problems occurring in the past, currently, or projecting issues that will arise in the future as suggestions and constructive criticism. On the one hand, it is a form of community solidarity in mobilizing diverse aspirations for humanitarian aid. Nevertheless, on the other hand, it is ridden by the oligarchs of the political elite to gain votes. Moreover, on the outside, it stretches the actions of Islamic radicalism.